PENGARUH KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN SKIN CARE - Zuraidah Zuraidah; Angelia Nesma Yunika Putri (Program Studi Ekonomi Syariah Fakultas Ekonomi dan Bisnis Islam IAIN Kediri, 2020)
To satisfy customer needs and desires, there is one thing that every company must pay attention to when it comes to competing in the market. When choosing a product, customers usually make a critical assessment of the product to be purchased. Customers certainly want to get quality products according to the price paid. When deciding to purchase a product, it means that the customer has already decided what to buy, decided to buy or not, decide when and where they will buy, and decide how they will buy it. This study aims to determine the effect of product quality on purchasing decisions for skin care for consumers of Larissa aesthetic center Kediri branch. This study uses quantitative methods, the instrument in this study is a questionnaire given to respondents in the study. As for the population in this study are Muslim Consumers Larissa Aesthetic Center Kediri Branch. Probability sampling is the sampling technique used in this study, especially the simple random sampling technique. By using the Slovin formula, the researchers took a sample of 336 customers of Larissa Aesthetic Center Kediri Branch. The data were processed using descriptive data analysis, validity test, reliability test, classical assumption test, and hypothesis testing. The results showed that the regression equation formed was Y = 14.971 + 0.695X. According to the results of the t test it is known that the significance value of t (0.000 <0.05) with the results of t count 10.010 ≥ t table 1.6525 then H0 is rejected and H1 is accepted. This shows that product quality (X) has a positive and significant effect on purchasing decisions (Y). Based on the R square significance test that has been carried out, the results show that product quality has a significant effect on purchasing decisions by 0.530 or 53%. While the remaining 47% of purchase decisions are influenced by other variables not examined in this study, namely price, promotion and location.